Bibliometric Exploration of Bullying, Workplace Bullying, and Cyberbullying based on the Scientific Scopus Quantum - Vishwakama, Amit Kumar; Vishwakarma, Babita; Kumari, Pushpa (Indian Journal of Extension Education, 2025)
The study examines the landscape of bullying research, with a focus on workplace bullying and cyberbullying, utilizing Scopus-indexed publications from 1999 to 2024. A total of 20,406 publications were analyzed, including 14051 on bullying, 1,583 on workplace bullying, and 4,772 on cyberbullying. A bibliometric analysis was conducted using descriptive and network techniques to evaluate research productivity, trends, and collaborations. Key findings reveal that citations for bullying peaked in 2015, with workplace bullying research stabilizing, while cyberbullying research has shown sustained growth, reflecting the rise of digital platforms. Co-authorship analysis highlights strong international collaborations, with significant contributions from scholars like Espelage, D.L., and Einarsen, S., and leading research hubs in the U.S., U.K., and Scandinavia. Keyword co-occurrence identified critical themes such as workplace dynamics, adolescent victimization, and digital harassment. Emerging clusters in healthcare and family dynamics highlight underexplored domains that require further investigation. Future research should address bullying’s socio-psychological impacts and develop innovative methodologies to mitigate its evolving challenges in diverse settings.